Manajemen Komunikasi Pelestarian Budaya Seni Tari Pada Sanggar â€œPotre Konengâ€ Kabupaten Sumenep - Fauzuna , Hafidlatul (Unitri Press, 2021)
Today, the art of dance is being destroyed so that it requires preservation effort, in order to maintain its sustainability in the midst of society. This is what the Potre Koneng dance studio in Sumenep Regency is doing, namely by managing good communication so that efforts to preserve the art of dance take place well. This study uses a qualitative descriptive approach with data collection techniques using interviews, observation and documentation. The result showed that the communication management carried out in the Potre Koneng dance studio used an adult communication model which was analogous to the